2015
DOI: 10.1175/waf-d-14-00031.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Lightning Cessation Guidance Using Polarimetric Radar Data

Abstract: Polarimetric radar data are used to develop lightning cessation guidance for the Cape Canaveral area of central Florida. For this purpose, 80 nonsevere thunderstorm cells in 2012, mostly during the warm season, are analyzed. In-cloud and cloud-to-ground lightning data for the storms are obtained by combining information from the second-generation Lightning Detection and Ranging (LDAR-II) network and the National Lightning Detection Network (NLDN). Storms are tracked using the Warning Decision Support System–In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 77 publications
(74 reference statements)
3
23
0
Order By: Relevance
“…For a cloud base temperature less than 208C, the cloud depth must be at least 4 km and the cloud top temperature must be less than 2208C. These criteria were used as reasonable choices to ensure that the subgrid clouds were deep enough to have a mixed-phased layer supportive of lightning [e.g., Mansell et al, 2007;Bruning et al, 2014;Preston and Fuelberg, 2015].…”
Section: Lightning Assimilation Methodsmentioning
confidence: 99%
“…For a cloud base temperature less than 208C, the cloud depth must be at least 4 km and the cloud top temperature must be less than 2208C. These criteria were used as reasonable choices to ensure that the subgrid clouds were deep enough to have a mixed-phased layer supportive of lightning [e.g., Mansell et al, 2007;Bruning et al, 2014;Preston and Fuelberg, 2015].…”
Section: Lightning Assimilation Methodsmentioning
confidence: 99%
“…The non-inductive cloud charging mechanism, considered to be the main source of charges involved in lightning flashes within thunderstorms (Saunders, 1993;Latham et al, 2007), is mainly related to the collisions between ice crystals (positively charged) and graupel (typically associated with negative charge in the cloud), suggesting a relation between ice mass and lightning activity. Several studies over the last decade have shown that dual-polarization (DP) radar measurements may exhibit signatures that can be tied to lightning activity (e.g., López and Aubagnac, 1997;Goodman et al, 1989;Rutledge, 1996, 2000;Wiens et al, 2005;Preston and Fuelberg, 2015). López and Aubagnac (1997) showed that the evolution of lightning activity in an Oklahoma supercell thunderstorm that produced copious amounts of hail was related to the changes in the microphysical characteristics of the storm that were inferred from polarimetric radar measurements.…”
Section: N Roberto Et Al: Multi-sensor Analysis Of Convective Activmentioning
confidence: 99%
“…However, this algorithm failed to safely end advisories for nonisolated storms. The present study extends the work of Preston and Fuelberg [] (hereafter PF15) by examining nonisolated storms with the intent of providing increased understanding that together with future research may provide improved cessation guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Z H at À10°C is shown along with the WDSS-II storm outline of the cell (white line) and max Z H (52 dBZ) at this time. AfterPreston and Fuelberg [2015].…”
mentioning
confidence: 99%